A cost-minimization analysis of large overjet reduction with two removable functional appliances based on a randomized controlled trial. (4th November 2017) - Čirgić, Emina; Kjellberg, Heidrun; Petzold, Max; Hansen, Ken
Summary: Objective: The purpose of this study was to assess and relate the societal costs of reducing large overjet with a prefabricated functional appliance (PFA), or a slightly modified Andresen activator (AA), using a cost-minimization analysis (CMA). Design, settings, and participants: A multicentre, prospective, randomized clinical trial was conducted with patients from 12 general dental practices. Ninety-seven patients with an Angle Class II, division 1 malocclusion, and an overjet of ≥6 mm were randomly allocated by lottery to treatment with either a PFA or an AA. The PFA and AA groups consisted of 57 and 40 subjects, respectively. Blinding was not performed. Duration of treatment, number of scheduled/unscheduled appointments, and retreatment were registered. Direct and indirect costs were analysed with reference to intention-to-treat (ITT), successful (S), and unsuccessful (US) outcomes. Societal costs were described as the total of direct and indirect costs, not including retreatments. Interventions: Treatment with a PFA or an AA. Results: The direct and societal costs were significantly lower for the PFA than for the AA group. The number of visits was lower in the PFA group, when ITT was considered, and for the US cases as well. No difference in retreatment rate could be seen between the groups. Limitations: Costs depend on local factors and thus should not be generalized to other settings. Harms: No harms were detected during the study. Conclusion: The success rate of the both appliances was low. However, the PFA was the preferred approach for reduction of a large overjet in mixed dentition, since it minimized costs and there were no difference in clinical outcomes between PFA and AA. Registration: This trial was registered at 'FoU i Sverige' (http://www.fou.nu/is/sverige ), registration number: 97131. Protocol: The protocol was not published before trial commencement.